2018
DOI: 10.1111/joa.12780
|View full text |Cite
|
Sign up to set email alerts
|

Multivariate analysis of variations in intrinsic foot musculature among hominoids

Abstract: Comparative analysis of the foot muscle architecture among extant great apes is important for understanding the evolution of the human foot and, hence, human habitual bipedal walking. However, to our knowledge, there is no previous report of a quantitative comparison of hominoid intrinsic foot muscle dimensions. In the present study, we quantitatively compared muscle dimensions of the hominoid foot by means of multivariate analysis. The foot muscle mass and physiological cross-sectional area (PCSA) of five chi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
19
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(24 citation statements)
references
References 54 publications
(142 reference statements)
3
19
2
Order By: Relevance
“…These results correspond to that of Oishi [2009] which show that D5 has increased grasping capability in western lowland gorillas. Furthermore, Oishi et al [2018] have shown that abductor digiti minimi in gorilla are better developed, to some extent due to an additional muscle belly, which was found in this study too, compared to other great apes. Secondly, the peak summed flexor torques from proximal interphalangeal 4 (approx.…”
Section: Characteristics For Grasping Vertical Supportssupporting
confidence: 72%
See 3 more Smart Citations
“…These results correspond to that of Oishi [2009] which show that D5 has increased grasping capability in western lowland gorillas. Furthermore, Oishi et al [2018] have shown that abductor digiti minimi in gorilla are better developed, to some extent due to an additional muscle belly, which was found in this study too, compared to other great apes. Secondly, the peak summed flexor torques from proximal interphalangeal 4 (approx.…”
Section: Characteristics For Grasping Vertical Supportssupporting
confidence: 72%
“…The only published data on the functions of the interosseous muscles and lumbricals in gorilla feet are those in Ochiltree [1912], Preuschoft [1961], Hirasaki and Oishi [2018] and Oishi et al [2018] reflecting the difficulty of obtaining dissection data from these small muscles. Interosseous muscles are muscles that originate from metatarsals and insert onto proximal phalanges and metatarsophalangeal joints (and the extensor expansion for dorsal interossei) [Diogo et al, 2010].…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…These findings suggest that great apes can stiffen their midfoot joints during bipedal walking even without a longitudinal arch, undermining a major assumption of the dichotomy between human and great ape foot function. Based on the amended windlass model, the most likely mechanism behind this stiffening is activation of the foot muscles, whose attachments and sizes are generally similar in great apes and humans (Oishi et al, 2018). Although in vivo electromyography data are currently lacking, we predict that intrinsic foot muscle activity is closely correlated with foot stiffness during walking in great apes.…”
Section: Push-off and Propulsionmentioning
confidence: 85%